2000
DOI: 10.1046/j.1525-1438.2000.010004305.x
|View full text |Cite
|
Sign up to set email alerts
|

Overall 5-year survival rate and prognostic factors in patients with stage IB and IIA cervical cancer treated by radical hysterectomy and pelvic lymph node dissection

Abstract: The objective of this paper was to analyze the 5-year survival rate and prognostic factors for stage Ib and IIa cervical cancer treated by radical hysterectomy. A total of 366 patients with invasive cervical cancer treated by radical hysterectomy from June 1985 to June 1994 at Chonnam National University Hospital, Kwangju, Korea were retrospectively analyzed. Survival analysis was performed using the Kaplan-Meier estimator. Multivariate analysis was performed using the Cox proportional hazards regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 70 publications
(88 reference statements)
4
65
0
7
Order By: Relevance
“…The complication rates are low compared with those for radical hysterectomy 17 as are the recurrence rates. 17 The data are comparable with other published series, with five (4.1%) recurrences and four (3.3%) deaths in 123 women who were selected to have trachelectomy (Table 5). Excluding those who had abandoned procedures or completion treatment, there were three (2.7%) recurrences and two (1.8%) deaths in 112 women.…”
Section: Discussionmentioning
confidence: 91%
“…The complication rates are low compared with those for radical hysterectomy 17 as are the recurrence rates. 17 The data are comparable with other published series, with five (4.1%) recurrences and four (3.3%) deaths in 123 women who were selected to have trachelectomy (Table 5). Excluding those who had abandoned procedures or completion treatment, there were three (2.7%) recurrences and two (1.8%) deaths in 112 women.…”
Section: Discussionmentioning
confidence: 91%
“…The prognostic significance of AD histology remains unclear. It was previously reported that AD is less curable and associated with a shorter survival compared to SCC (7)(8)(9)(10)(11), whereas other studies reported no significant differences in prognosis between AD and SCC (12)(13)(14)(15)(16). Notably, the prognostic implications of applying the same treatment strategies on AD as for SCC have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with AdCa after RH is unclear, primarily because studies have been performed on small numbers of patients. Some of these studies found that patients with AdCa have poorer prognosis than do those with SCCa (Hopkins and Morley, 1991;Eifel et al, 1995;Look et al, 1996;Samlal et al, 1997;Lai et al, 1999;Kim et al, 2000;Nakanishi et al, 2000), whereas other reports found no differences in prognosis (AntonCulver et al, 1992;Miller et al, 1993;Shingleton et al, 1995;Grisaru et al, 2001;Ayhan et al, 2004;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009). Therefore, the prognosis after RH and the optimal management of AdCa are still a subject of debate.…”
mentioning
confidence: 99%